PERSEPSI MASYARAKAT DESA SABUNG TERHADAP PEMBANGUNAN KEBUN RAYA KABUPATEN SAMBAS - Santoso, Eko Budi; Zainal, Sofyan; Yani, Ahmad (Universitas Tanjungpura, 2014)
Development of botanical gardens as a government effort to maintain the natural resource ecosystems may be affected by changes in the condition and development of social behavior in the surrounding communities. The purpose of this study was to determine the public's perception of community Sabung village towards development botanical garden in Sambas district. Data were collected by survey method by interviewing people in two villages located in the village Sabung. Respondents were selected by purposive sampling. the community is more than 3 years residing in the village Sabung. The results showed that there are differences in the perception of the botanical garden development. The public has a positive perception, and being negative about the development of botanical gardens Sambas district. However, the overall development of society agrees with Sambas district botanical gardens and take positive impact on the forest and surrounding communities. This difference in perception may be due to differences in the level of knowledge and lack of socialization by took instance on the development and benefits of botanical gardens. Key word : Perception, community and development botanical garden